Sistem Pendukung Keputusan Pemilihan Supplier Toserba Terbaik Menggunakan Metode Objective Weighting-TOPSIS (OWH-TOPSIS) - Izka, Ade Adyatna; Sulistiani, Heni (Journal of Information System Research (JOSH), 2024)
Convenience store suppliers are important partners in the retail supply chain, responsible for providing a wide range of daily necessities, from groceries to household items, directly to retailers or convenience store owners. The problem in the research on selecting the best convenience store supplier lies in the complexity of evaluating and balancing various criteria that affect supplier performance. Each supplier has different advantages and disadvantages in terms of product quality, price, delivery time, product availability, flexibility in ordering, and payment terms. The main challenge in this study is to determine the right weight for each criterion so that the selection decision can reflect the strategic needs of the convenience store objectively and accurately. The Objective Weighting-TOPSIS (OWH-TOPSIS) method is a modification of the TOPSIS method that combines an objective weighting approach to objectively determine the weight of the criteria. OWH-TOPSIS is an approach in a decision support system that combines objective weighting with the TOPSIS method to effectively assess and prioritize alternatives. The results of the supplier assessment ranking show that Supplier 3 and Supplier 7 are in the top position with very close preference scores, namely 0.9462 and 0.946 respectively, indicating that they are both the best choices based on the set criteria. Followed by Supplier 5 and Supplier 13 with identical scores of 0.9253, showing excellent performance but slightly below the top two suppliers. Supplier 1 is in fifth position with a score of 0.913, still in the very good category but slightly behind compared to the top four suppliers. This ranking provides a clear picture of each supplier's relative ranking in terms of meeting the evaluation criteria.